2020
DOI: 10.1002/jgh3.12349
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of non‐alcoholic fatty liver disease and non‐alcoholic steatohepatitis in Japan: A focused literature review

Abstract: Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) represent a growing unmet medical need and an increasingly prevalent cause of cirrhosis, hepatocellular carcinoma (HCC), and death in Japan. The aim of this review was to characterize the epidemiology of NAFLD and NASH in Japan. An English and Japanese literature search was conducted in PubMed, Embase, and ICHUSHI Web, identifying 6553 studies, 67 of which were included. Prevalence of NAFLD in the Japanese population rose from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 70 publications
(431 reference statements)
1
11
0
Order By: Relevance
“…Although there was no significant difference in OS (P = 0.057), OS in the NAFLD/NASH-HCC patients treated with lenvatinib was very favorable (20.5 months) and tended to be better than that in the Viral/Alcohol HCC cases (16.9 months). It was recently proposed by Hessheier et al that metabolic factors may be risk factors for development of liver diseases and cirrhosis 32 , while Eguchi et al found “lean-NASH” (non-obese NASH, body mass index: BMI < 25 kg/m 2 ) existing in 20% to > 35% in patients in Japan 33 . Of the present cryptogenic HCC patients (n = 26), diabetes was observed in 44.4% (n = 12), hypertension in 51.9% (n = 14), and overweight (BMI ≥ 25 kg/m 2 ) in 25.9% (n = 7), while 70.4% (n = 19) had at least one of those co-factors (Supplemental Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant difference in OS (P = 0.057), OS in the NAFLD/NASH-HCC patients treated with lenvatinib was very favorable (20.5 months) and tended to be better than that in the Viral/Alcohol HCC cases (16.9 months). It was recently proposed by Hessheier et al that metabolic factors may be risk factors for development of liver diseases and cirrhosis 32 , while Eguchi et al found “lean-NASH” (non-obese NASH, body mass index: BMI < 25 kg/m 2 ) existing in 20% to > 35% in patients in Japan 33 . Of the present cryptogenic HCC patients (n = 26), diabetes was observed in 44.4% (n = 12), hypertension in 51.9% (n = 14), and overweight (BMI ≥ 25 kg/m 2 ) in 25.9% (n = 7), while 70.4% (n = 19) had at least one of those co-factors (Supplemental Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently been proposed by Hessheier et al that metabolic factors may be risk factors for development of liver diseases and cirrhosis 29 , while Eguchi et al found "lean-NASH" (non-obese NASH, body mass index: BMI <25 kg/m 2 ) existing in 20% to >35% in patients in Japan 30 . Of the present cryptogenic HCC patients (n=26), diabetes was observed in 44.4% (n=12), hypertension in 51.9% (n=14), and overweight (BMI ≥25 kg/m 2 ) in 25.9% (n=7), while 70.4% (n=19) had at least one of those co-factors (Supplemental Table S2).…”
Section: Discussionmentioning
confidence: 99%
“… [9] , [10] , [11] , [12] , [13] Risk factors for NAFLD are metabolic in nature and include obesity, insulin resistance, type 2 diabetes, hypertension, and dyslipidaemia. 9 , 10 , [13] , [14] , [15] , [16] Male sex and older age are also risk factors for NAFLD. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%